Reflection on the Circle Line and Express Line in Shanghai Urban Rail Transit Network Planning - WANG Zhongqiang; CHEN Bizhuang; SHEN Yunzhang; LYU Zhengyu; LI Ying; LONG Li (Chengshi guidao jiaotong yanjiu)
［Objective］Since the implementation of the Shanghai Master Plan (2017-2035), with the development of five new Shanghai towns (Jiading, Qingpu, Songjiang, Fengxian, and Nanhui) and the Yangtze River Delta integration ascending to national strategies, Shanghai urban rail transit planning network is also undergoing further adjustments. Among them, circle lines and express lines (shorten as circle/express lines) are the focus of discussion, and it is necessary to study the functional planning, passenger flow characteristics and planning principles of circle/express lines. ［Method］Using the passenger flow data of existing urban rail transit lines, the characteristics and functions of circle/express lines passenger flow are analyzed; by comparing the previous research conclusions and actual operation status of circle/express lines, the planning experience of circle/express lines is summarized. Based on the urban development plan requirements in the new era, the shortcomings of circle/express lines in the existing plan are analyzed, and the functional requirements and planning principles of them in the new round of plan adjustments are proposed. ［Result & Conclusion］The passenger flow carried by the circle line is divided into three categories: passenger flow along line service range, transit passenger flow and arrival/departure passenger flow of the line. The corresponding circle line can play service functions for the above three scenarios. In addition to the existing circle line—Shanghai Rail Transit Line 4, the second circle line can be planned to meet the needs of passenger flow distribution along the line. It is recommended that the second circle line can be located between the middle and outer ring roads, making use of the planned Shanghai Rail Transit Line 26, and better closer to the middle ring line. The planning of express lines from suburbs to central urban area should be further strengthened. There are direct access and hub access two forms of express lines entering the central urban area network. Hub access requires highly convenient hub station for this purpose, while direct access to the network features relatively high cost. The corresponding indicator calculation method of express line travel time may be selected based on the connection closeness degree between new towns and the central urban area.